Cone Tessellation Model for Three-Dimensional Networks - Sarisin, Gozde; Salamah, Muhammed (Springer-Verlag Berlin, 2011)
Wireless terrestrial networks are usually designed in 2D plane, but in real life they form 3D space. In these networks, node placement strategy is one of the most important design problems. The idea is to deploy a number of nodes in an effective way to achieve communication between them. The volumetric quotient, which is the ratio of the transmission range to the sensing range of each node, is used as the main measure of the placement strategy. Researchers use polyhedrons to model 3D networks. As the volumetric quotient increases, we need less number of nodes for full coverage. In this paper, we proposed a cone model which gives a higher volumetric quotient than polyhedrons. The inspiration comes from satellite foot-print. For example, the number of nodes for truncated octahedron placement strategy is found to be 46.35% higher than the cone placement strategy. We also achieved full coverage with cone tessellation.
3rd International Conference on Wireless and Mobile Networks (WiMo 2011) -- JUN 26-28, 2011 -- Ankara, TURKEY
Keywords: Modeling; 3D networks; tessellation; Kelvin's Conjecture; Kepler's Conjecture; Sensor Networks